KELAYAKAN MODUL MATERI PELUANG DENGAN METODE JOYMATH COGNITIVE BEHAVIORAL UNTUK MENURUNKAN KECEMASAN MATEMATIKA DAN MENINGKATKAN SELF-EFFICACY SISWA - Hetty Marhaeni, Nafida; Khuzaini, Nanang; Rafi Fajar Rizky, Muhammad; Yuniasanti, Reny; Akbar, Mutaqin; Sartika Sari, Dian; Dangin, Dangin (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
The purpose of this research is to develop a module to reduce math anxiety and increase students’ self-efficacy in opportunity materials. The type of research used in this study is R&D (Research and Development) using the ADDIE model. The ADDIE development model is a development model that has five stages of development, namely analysis, design, development, implementation, and evaluation). The data sources and subjects in this study are material experts, media experts, teachers, and 1328 students from 24 junior high schools in Yogyakarta City. The data collection techniques used in this study are interviews, observations, Focus Group Discussions (FGD), and questionnaires. The results that have been implemented show that the product developed, namely the opportunity material module to reduce mathematical anxiety and increase students’ self-efficacy, is suitable for use in mathematics learning. The development of the opportunity material module is based on the results of the analysis, which shows that students need learning media that can help them reduce mathematical anxiety and increase self-efficacy. The decision-making on product feasibility is based on the results of assessment analysis from validators, material experts, and media experts who show that the material module is an opportunity to reduce mathematical anxiety and increase students’ self-efficacy, which is declared to be very valid. The suggestion for previous research is that research needs to be continued at the implementation stage and the evaluation stage.